Smart Energy Coordination Platform for Rural Public Facilities: Multi-Facility Load Optimization and Smart Control System - Rahma Niar; Zuraidah Tharo; Nur Fadilah Rahmadani (ITEJ (Information Technology Engineering Journals), 2025)
Rural public facilities in Indonesia face significant energy efficiency challenges due to inadequate management systems, aging infrastructure, and limited technical capacity. This study develops a smart energy coordination platform integrating IoT sensors and wireless communication networks for five public facilities in Petumbukan Village, North Sumatra. Six-month continuous monitoring using power quality analyzers and IoT data loggers revealed 310.7 kWh/day total consumption with 0.43 load factor, 40.7 kW peak demand, and 1.27 diversity factor across facilities. Comprehensive energy audit identified 17.7 kW total losses (43.5% of peak load), with lighting inefficiency representing the primary concern at 8.5 kW (20.9% of system load). The proposed four-layer IoT architecture implements smart meters, environmental sensors, LoRaWAN communication, and edge computing devices for real-time monitoring and automated control. Multi-facility coordination algorithms leverage load diversity to achieve 22% annual energy savings (56,327 kWh) through optimized scheduling and demand management. System performance demonstrates 15% peak demand reduction, load factor improvement from 0.43 to 0.52, and sub-5-minute response times for automated load adjustments. The platform provides a technically feasible and replicable framework for rural electrification optimization in developing countries, addressing the gap between urban-focused smart grid solutions and rural infrastructure constraints.